Lipid profile of artisanal Minas cheese from certified regions in the state of Minas Gerais, Brazil - Dargère, Adélia Ferreira; Pinto, Sandra Maria; Silva, Jonas Guimarães e; Garbossa, Cesar Augusto Pospissil; Batista, Diogo Santos; Correia, Laryssa Fernandes; Marçal, Joanna Oliveira; Faria, Peter Bitencourt (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to determine the fatty acid profile of artisanal Minas cheese from seven certified regions in the state of Minas Gerais, Brazil. A total of 78 samples were collected in regions where the producers were registered by Instituto Mineiro de Agropecuária. For lipid profile determination, different cheese varieties from the following regions were analyzed: Canastra, Serro, Araxá, Serra do Salitre, Triângulo Mineiro, Campo das Vertentes, and Cerrado. The lipid profile of Serra do Salitre and Araxá cheeses was similar in caproic acid (C6:0), total polyunsaturated fatty acids, and ratio of polyunsaturated and saturated fatty acids. In the other regions, lipid profile differed due to associations with specific fatty acids, such as those of the cheeses from Triângulo Mineiro with C20:5n3, of Cerrado with C20:4n6, of Canastra with C8:0, of Serro with C22:2 and C22:6n3, and of Campo das Vertentes with C17:0, C18:0, and C20:0. The fatty acid profile and nutritional indices related to the lipid profile of artisanal Minas cheeses differ according to the region of origin. The content and profile of omega 3 fatty acids are significant parameters to differentiate artisanal Minas cheeses. Serro artisanal Minas cheese presents superior nutritional indices concerning fatty acid profile than the other studied cheeses.